A new option for laparoscopic spleen-preserving distal pancreatectomy: three cases with splenic artery preservation and resection of the splenic vein. Issue 4 (3rd April 2022) - Okuno, Masataka; Shimizu, Yasuhiro; Senda, Yoshiki; Natsume, Seiji; Kawakatsu, Shoji; Ito, Seiji; Komori, Koji; Abe, Tetsuya; Misawa, Kazunari; Ito, Yuichi; Kinoshita, Takashi; Higaki, Eiji; et al.
Abstract: There are two techniques for a spleen-preserving distal pancreatectomy (SPDP): SPDP with splenic vessel preservation, and SPDP with splenic vessel resection. In some cases, although the splenic artery (SpA) can be preserved, the splenic vein (SpV) must be resected. We report the short- and long-term outcomes of three patients who underwent a new technique of laparoscopic SPDP with SpA preservation and SpV resection (SPDP-VRes). A grade B pancreatic fistula, which occurred in two patients, was successfully treated with drainage tube management. In all cases, the omental branches of the left gastroepiploic vein functioned as a drainage vein, and there was no splenomegaly, thrombocytopenia, or varix formation during the follow-up period (19 months to 5 years). Patients undergoing laparoscopic SPDP-VRes had no severe complications during the follow-up period; preserving the left omental branch is a key to this procedure. Laparoscopic SPDP-VRes might be a useful treatment option for patients undergoing SPDP.